Dependency and Biodiversity: Challenges in Implementing Circular Economies and Bioeconomies in Southern Latitudes - Catalan Duran, Patricia Isabel (2023)
Climate change poses challenges to Southern latitudes. The pursuit of new economic models that counter unsustainable consumption habits leads to rethinking the relationship between sustainable economic development and emerging initiatives in the Southern latitudes, considering the implementation of circular economies and bioeconomies. However, these initiatives must not overlook the social, cultural, and historical realities of Latin America. These realities appeal to a dependent and multicultural context, presenting potential paths for the development of circular economies and bioeconomies.